Accessory and cavitated uterine mass: a rare case - Chauhan, Anjali; Perhar, Ramona; Chaudhary, Shikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Accessory and cavitated uterine mass (ACUM) are a rare congenital Müllerian duct anomaly characterized by a non-communicating uterine mass containing functional endometrial tissue, typically located near the insertion of the round ligament. It predominantly affects adolescents and young women presenting with severe dysmenorrhea or cyclic pelvic pain unresponsive to medical therapy. Due to its similarity in presentation to adenomyosis, fibroids, and rudimentary uterine horn, ACUM is frequently misdiagnosed. We report a case of a reproductive-age woman with intractable dysmenorrhea since adolescence that did not improve with hormonal treatment. Preoperative magnetic resonance imaging (MRI) suggested ACUM, and the patient underwent laparoscopic ACUM removal. Intraoperative findings revealed an isolated cavitated mass at the left round ligament. Histopathological examination confirmed the presence of functional endometrial lining surrounded by hypertrophic myometrium, consistent with ACUM. Postoperatively, symptoms resolved completely. Early recognition of ACUM is essential in young women with unexplained dysmenorrhea, and surgery remains the definitive treatment.